EVALUASI SUSUT DAYA AKIBAT DAMPAK HARMONISA PADA TRAFO DISTRIBUSI PT. PLN (Persero) UP3 SURABAYA SELATAN ULP NGAGEL SURABAYA - Suwarno, Nastiti Viononny; Utomo, Teguh; Wijono, n/a (Jurnal Mahasiswa TEUB, 2024)
Harmonic is a disturbance in the electric power distribution system caused by current and voltage wave distortion. This distortion generally occurs due to the presence of waves with different frequencies, which is the result of multiplying integers with a frequency of 50 Hz. Transformers, which are important tools and often used in electric power systems, can be influenced byharmonics and experience negative impacts. Harmonics can affect all components in an electric power distribution system, although the resulting effects and impacts vary. However, generally, harmonics can cause performance degradation and may also damage distribution components. Because of this, it is important to supervise the impact of harmonics on distribution transformers, which are very important components in electric power systems. If the harmonic level is above the specified limit, it will cause several problems, one of which is the loss in the distribution transformer. To determine the effect of harmonics on power losses on several distribution transformer samples, it is done using the harmonic measurement method on each distribution transformer sample in the ULP Ngagel area with the help of the HIOKI CM-3286-50 multimetre for further data processing. The data used is in the form of the results of measuring power, current, voltage, and THD (Total Harmonic Distortion) of current and voltage. The results obtained after data processing are, can determine the difference in efficiency, loss-loss, effect of current before and after being affected by harmonisa, which harmonisa has a negative effect on the transformer in the form of decreasing efficiency, increasing loss-loss, heating of the transformer caused by excessive current, and so on. Keywords: distribution transformator, power losses, harmonic, total harmonic distortion